Festas religiosas: identidade, memória, música e desenvolvimento nos festejos da missão em Dianópolis – TO - Lopes, Dayhan Deives Camelo (Universidade Federal do Tocantins, 2021)
This work analyzes the identity construction in the religious festivals of Dianópolis that take place in the Mission, rural area of the city, from the theoretical contribution of Stuart Hall (2004), Michael Pollak (1992) and a few from Arturo Escobar ( 1999). from the memory of the participating actors, we intend to report the party to the local identity in order to contribute to valuing the elements of the festive scene, such as music, dances, rhythms and local agents analyzing as variants between faith and development present in the festive ritual. The festivities move a network of people and have their own potential to generate resources for both the municipality and the population. The religious festivals will be updated and incorporating modernizing elements. The festive space that was once a place of great pain and suffering, today has another meaning for the pilgrims who frequent the place. Among these transformations, the insertion of women in different functions in the “folias” was highlighted in this work. The musicality present in the festive spaces of Dianópolis provided for this work an analysis about the local identity, as an important element in the re-signification of the festive space, of the local arrangements and, also, as an available reserve, which generates and attracts construction resources. Thus, walking the paths of religious festivals in Dianópolis is an immersion in a multiple process of gradual production of meanings and knowledge building.